Transepithelial elimination in sarcoidosis: a frequent finding. (20th November 2013) - Ismail, Aimen; Beckum, Kathleen; McKay, Kristopher
Abstract Background Transepithelial elimination is a process by which dermal materials are expelled through an active epithelial‐dermal connective tissue interaction. It has been described as a regular or sporadic occurrence in a variety of dermatologic conditions, including sarcoidosis. Observation Our patient demonstrated a rare presentation of sarcoidosis involving the genital region, with histopathologic evidence of transepithelial elimination of granulomas. This prompted us to conduct the first case series documenting the frequency of transepithelial elimination in sarcoidosis. Methods Slides of skin biopsies from patients (n = 50) with cutaneous sarcoidosis from the University of Alabama at Birmingham were evaluated for transepithelial elimination. Transepithelial elimination was defined as epithelial channel formation with a sarcoidal‐type granuloma completely surrounded by squamous epithelium on the section examined. Results Transepithelial elimination was found in 9 of 50 cases (18%). Conclusion This is the first report of transepithelial elimination in a lesion of sarcoidosis localized to the vulvar area, and one of only six reports in the English literature documenting cutaneous sarcoidosis with histopathologic evidence of transepithelial elimination. These reports are reviewed herein. Surprisingly, the results from this case series indicate that transepithelial elimination is more common in cutaneous sarcoidosis than one may surmise from the current literature.